THE ROLE OF INVESTORS IN IMPROVING THE EFFECTIVENESS OF METHODS OF IMPROVING THE SYSTEM OF CORPORATE GOVERNANCE (Academicia Globe: Inderscience Research, 2023)
This article explores the crucial role investors play in enhancing the effectiveness of methods employed to improve corporate governance. By actively participating in the decision-making process and advocating for transparency and accountability, investors have the power to influence corporate behavior and promote responsible governance practices. This article investigates various methods utilized by investors, analyzes their impact, and highlights the importance of their involvement in shaping the corporate landscape.